Acetone sensing and modeling through functionalized Ag-catalysts and CNTs via low cost metal-organic framework-derived ZnO nanostructures. Issue 3 (1st February 2021) - Khan, Farhat Ullah; Ansar, M. Tamoor; Ullah, Zaka; Ali, Rozi; Waseem, Muhammad; Mustafa, Ghulam M.; Atiq, Shahid; Naseem, Shahzad
Abstract: Cost-effective synthesis, portability, quick response and fascinating features of semiconducting metal oxide sensors have drawn much accredited to be utilized in wide variety of potential sensing applications. Herein, flexible acetone sensor was fabricated through spray coating method using different conductive inks of carbon nanotubes (CNTs), zinc oxide (ZnO) and silver (Ag) nanoparticles solutions on cellulose paper. Morphological analysis revealed the fiber like morphology of cellulose over which CNTs, ZnO and Ag nanoparticles are uniformly distributed. The energy dispersive X-ray spectroscopic analysis was performed to observe the elemental composition in the as-prepared samples. The recovery time toward acetone was greater for CNTs/Ag acetone sensor at 95% as compared to CNTs/ZnO/Ag sensor. Additionally, sensing time of the samples towards acetone was measured and the observed response time was greater for CNTs/ZnO/Ag (0.52 s) acetone sensor as compared to CNTs/Ag sensor (0.41 s). Hence, CNTs/ZnO/Ag can be easily employed for sensing applications due to quick response.